3D Interdigital Au/MnO2/Au Stacked Hybrid Electrodes for On‐Chip Microsupercapacitors. Issue 22 (26th April 2016) - Hu, Haibo; Pei, Zhibin; Fan, Hongjin; Ye, Changhui
Abstract : On‐chip microsupercapacitors (MSCs) have application in powering microelectronic devices. Most of previous MSCs are made from carbon materials, which have high power but low energy density. In this work, 3D interdigital Au/MnO2 /Au stacked MSCs have been fabricated based on laser printed flexible templates. This vertical‐stacked electrode configuration can effectively increase the contact area between MnO2 active layer and Au conductive layer, and thus improve the electron transport and electrolyte ion diffusion, resulting in enhanced pseudocapacitive performance of MnO2 . The stacked electrode can achieve an areal capacitance up to 11.9 mF cm −2 . Flexible and all‐solid‐state MSCs are assembled based on the sandwich hybrid electrodes and PVA/LiClO4 gel electrolyte and show outstanding high‐rate capacity and mechanical flexibility. The laser printing technique in this work combined with the physical sputtering and electrodeposition allows fabrication of MSC array with random sizes and patterns, making them promising power sources for small‐scale flexible microelectronic energy storage systems (e.g., next‐generation smart phones). Abstract : Flexible microsupercapacitors with 3D interdigital Au/MnO2 stacked hybrid electrodes are fabricated on laser printed plastic substrates and exhibit a large areal capacitance up to 11.9 mF cm −2 .